Studies directed toward the exploitation of vicinal diols in the synthesis of (+)-nebivolol intermediates - Devi, Runjun; Das, Sajal Kumar (Beilstein Journal of Organic Chemistry, 2017)
While the exploitation of the Sharpless asymmetric dihydroxylation as the source of chirality in the synthesis of acyclic molecules and saturated heterocycles has been tremendous, its synthetic utility toward chiral benzo-annulated heterocycles is relatively limited. Thus, in the search for wider applications of Sharpless asymmetric dihydroxylation-derived diols for the synthesis of benzo-annulated heterocycles, we report herein our studies in the asymmetric synthesis of (R)-1-((R)-6-fluorochroman-2-yl)ethane-1,2-diol, (R)-1-((S)-6-fluorochroman-2-yl)ethane-1,2-diol and (S)-6-fluoro-2-((R)-oxiran-2-yl)chroman, which have been used as late-stage intermediates for the asymmetric synthesis of the antihypertensive drug (S,R,R,R)-nebivolol. Noteworthy is that a large number of racemic and asymmetric syntheses of nebivolol and their intermediates have been described in the literature, however, the Sharpless asymmetric dihydroxylation has never been employed as the sole source of chirality for this purpose.
Keywords: dihydroxylation; epoxide-ring opening; heterocycles; nebivolol; syn-epoxide